Perancangan Sistem Pengambilan Keputusan Pemesanan Barang dengan Harga Fluktuatif pada CV X - Satria Nalapradipta; Tanti Octavia; I Gede Agus Widyadana (Jurnal Titra, 2019)
This research was conducted at CV X, an aluminum distributor in Surabaya which determines the quantity of ordered goods only by estimation. The fulfillment of inventory is determined by the owner of CV X, considering the fluctuations in aluminum prices and inventory in the warehouse. Ordering goods always done in excessive quantities. It makes the items in the warehouse pile up. This research uses ABC classification, ROP, and EOQ which consider the price fluctuation. The result of EOQ and EOP will be an input in the information sistem. Information sistem are designed to be able to calculate the new EOQ which taking price fluctuation into account. The proposed method produces a greater value of efficiency and a decrease in total.